Reparation for Victims of Human Rights Violations and Crimes Against Humanity in Ecuador - Solís, María Cristina (2018)
In May of 2007, former President Rafael Correa created a Truth Commission for Ecuador (CVE), assigned with the task of clarifying the events of political violence that took place in the country between 1984-2007. In June of 2010, with the report of the Commission submitted, the Ecuadorian State began to take a series of actions that had as their objective to acknowledge the responsibility in the events that took place and to implement reparation measures, justice remedies and administrative reforms. This article aims to approach the way in which “making memory” of the investigated events by the CVE was used as a supporting argument for the definition and promulgation of reparation policies for victims and/or family members, as well as the way in which these public policies gained acceptance from the authorities called upon to enforce them.